Pembantaran Pelaku Tindak Pidana yang Menderita Gangguan Jiwa dalam Tinjauan Hukum Pidana Islam Studi Kasus di Polrestabes Surabaya - Sodiq, Djakfar (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2020)
The paper aims to find out the Islamic Criminal Law's perspective on the postponement of the penal sentence on the criminal offenders who suffer mental disorders at the Surabaya Police Headquarters. At the end of the paper, it is concluded that the implementation of postponement arouses two main points of discussion. First, it is seen from the condition and fitness of the perpetrator that is the effect of mental disorders on the criminal. According to the opinions of ulama 'Malikiyah and Hanafiyah, the insane condition that occurred before the judge's decision could stop the court examination process and postpone it until the insane state disappeared. Their reason is that to impose a sentence requires a taklif, which must be present when conducting an examination. Second, because of postponing penal sentence on the criminal offender who has a mental disorder aims to facilitate the police to obtain clarity on a criminal case committed by the perpetrator or the suspect, so whether the suspect can be held accountable for the criminal act or not is in the interest of smooth examination. Therefore, in the view of Islamic Criminal Law, it is appropriate to postpone the legal sentence, because it is based on the text related to the prohibition of carrying out punishment if still in doubt (shubhat).